Analisis Kesulitan Belajar Siswa Dalam Menyelesaikan Soal Matriks - Rosliana Siregar; Suwanto Suwanto; Muhammad Daut Siagian (Universitas Asahan, 2021)
AbstractAnalysis of learning difficulties in mathematics in class X matrix material which is rarely done by teachers because of their busyness in fulfilling their teacher administration, is the reason for this research. The research method used is descriptive research with the aim of explaining the conditions of student learning difficulties that occur in understanding the matrix material. The instruments used were learning observations with a Likert scale, a matrix test with 20 multiple choice items and interviews with 10 questions. Before using these three instruments, expert validation was carried out, and trials for matrix test instruments were carried out to determine the level of reliability and validity of the instrument. The population of this study was 95 students and only 10 students were used as research samples, the sample selection was using the purposive sample method. The results obtained were 63.64% of students had difficulty mastering the matrix concept, due to insufficient prerequisite material. Keywords: difficulty in learning mathematics; matrix AbstrakAnalisis kesulitan belajar matematika pada materi matriks kelas X yang jarang dilakukan oleh guru karena kesibukan mereka dalam memenuhi administrasi keguruannya mereka, menjadi alasan penelitian dilakukan. Metode penelitian yang digunakan adalah penelitian deskriptif dengan tujuan menjelaskan kondisi kesulitan belajar siswa yang terjadi dalam memahami materi matriks. Instrumen yang digunakan adalah observasi pembelajaran dengan skala likert, tes matriks dengan 20 item soal multiple choice dan wawancara dengan 10 pertanyaan. Sebelum digunakan ketiga instrumen ini dilakukan validasi ahli, dan uji coba untuk intrumen tes matriks untuk mengetahui tingkat reabilitas dan validitas instrumen. Populasi penelitian ini sebanyak 95 siswa dan hanya 10 siswa dijadikan sampel penelitian, pemilihan sampel dengan metode sample purposive. Hasil yang diperoleh sebanyak 63,64% siswa kesulitan untuk menguasai konsep matriks, dikarenakan materi prasyarat yang belum memadai. Kata kunci: kesulitan belajar matematika; matriks